Climate change adaptation and mitigation initiatives for agriculture in East Africa - Nyasimi, Mary; Radeny, Maren A.O.; Kinyangi, James (2013)
National governments across East Africa are in the process of formulating and implementing adaptation and mitigation strategies to assist farmers cope with climate change. These include formulating actions, frameworks and programs to address climate change and embedding these within the long-term national development plans. This working paper provides understanding of the current state of national climate change adaptation and mitigation efforts in Ethiopia, Kenya, Tanzania and Uganda for agriculture and provides baseline information for subsequent assessments of climate change adaptation and mitigation. In each country, specific government departments such as Environmental Protection Authority (Ethiopia), Ministry of Environment, Water and Mineral Resources (Kenya), Vice President‘s Office (Tanzania) and Ministry of Water and Environment (Uganda) are mandated to coordinate climate change initiatives. In all countries, the Ministry of Agriculture is the focal point for all climate change initiatives related to agriculture. Agricultural Sector Development Plans that provide strategies to boost agricultural productivity and spur economic growth have been prepared either as standalone plans or as part of National Development Plans (NDP). Irrigation, capacity building, enhancing private-public partnership for market development, and creating legal and regulatory environment that can attract investments are some of the priority areas identified for attention in agriculture to enhance climate resilience.